Leaf from a 1601 Bible, verso. - Barker, Robert, d. 1645. (Tufts University, Tisch Library, 2013)
Layout: Printed in two columns of 65 lines.; Originally printed in London by Robert Barker, 1601. 1 leaf (printed on both sides) ; 32 cm.; Comprising of the first 42 lines from John, chapter 7.